Guarantees of the rights of land users of land plots for individual housing construction - Krasutski, Heorhi V. (Journal of the Belarusian State University. Law, 2024)
The author of the article examines the problems in the field of guarantees of the rights of land users when using land plots for individual housing construction in the aspect of the principle of social justice and digitalisation of various fields of activity. Theoretical conclusions and proposals for improving legislation in order to ensure accessibility, efficiency and rationality of land use for individual housing construction are formulated.